Microplastic pollution in wild commercial nekton from the South China Sea and Indian Ocean, and its implication to human health. (May 2021) - Chen, Jin-Can; Fang, Chao; Zheng, Rong-Hui; Hong, Fu-Kun; Jiang, Yu-Lu; Zhang, Min; Li, Yuan; Hamid, Fauziah Shahul; Bo, Jun; Lin, Long-Shan
Abstract: Marine biota, especially commercially important species, serves as a basis for human nutrition. However, millions of tons of plastic litter are produced and enter the marine environment every year, with potential adverse impacts on marine organisms. In the present study, we investigated the occurrence and characteristics of microplastic (MP) pollution in the digestive tracts of 13 species of wild nektons from 20 stations sampled in the South China Sea (SCS) and the Indian Ocean (IO), and assessed the human health risks of MPs. The detection rate of MPs ranged from 0.00% to 50.00% from the SCS, which was dramatically lower than that from the IO (10.00–80.00%). The average abundance of MP was 0.18 ± 0.06 items g wet weight −1 (ww −1 ) in the SCS, which was significantly lower than that in the IO with a concentration of 0.70 ± 0.16 items g ww −1 . Most MPs were fibers in type, black in color, and polyester (PES) in polymer composition in both the SCS and IO. Interestingly, distinct profiles of MP pollution were found between the benthic and pelagic nektons: 1) The predominant MP composition was PES in the benthic nektons, whereas polyamide (PA) accounted for a larger part of the total MP count in the pelagic nektons within the SCS; 2) The abundance of MP in the benthic nektons (0.52 ± 0.24 items individual −1 ) was higher than that in the pelagic nektons (0.30 ± 0.11 items individual −1 ). Accordingly, the mean hazard score of MPs detected in the benthic nektons (220.66 ± 210.75) was higher than that in the pelagic nektons (49.53 ± 22.87); 3) The mean size of the MP in the pelagic nektons (0.84 ± 0.17 mm) was larger than that in the benthic nektons (0.49 ± 0.09 mm). Our findings highlight the need to further investigate the ecological impacts of MPs on wild nekton, especially commercially important species, and its potential implications for human health. Graphical abstract: Image 1 Highlights: MPs were detected in 90.00% of all the sampling sites. The detection rate of MPs in the wild nektons from the SCS was significantly lower than that from the IO. The average abundance of MPs in the IO was dramatically higher than that in the SCS. Most MPs were fibers in type, black in color and PES in polymer composition.